Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/shk.0b013e31825de6a3
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death 1 Expression as a Marker for Immune and Physiological Dysfunction in the Critically Ill Surgical Patient

Abstract: Programmed death 1 (PD-1) is an inhibitor protein receptor for the immune system and has been shown to be upregulated in animal models of critical illness as well as after trauma and in burn victims in humans. It is believed that PD-1 may play a role in the immune dysfunction seen in surgical critical illness. However, although prior studies have associated changes in PD-1 expression with altered immune cell function, it is not known if a correlation with clinical status exists. We therefore aimed to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…We noted that this migration was PD-1 dependent. PD-1 is a checkpoint molecule which plays a critical role in both experimental sepsis as well being associated with outcomes in critically ill septic patients(15). It is predominantly considered a co-inhibitory molecule located primarily on T-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that this migration was PD-1 dependent. PD-1 is a checkpoint molecule which plays a critical role in both experimental sepsis as well being associated with outcomes in critically ill septic patients(15). It is predominantly considered a co-inhibitory molecule located primarily on T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill septic patients, acute lung injury mortality was associated with increased PD-1 expression on circulating T-cells. An association was also noted between APACHE II scores and expression of PD-1(15). In murine sepsis models, PD-1 affect pulmonary lymphocyte trafficking as well development of acute lung injury(16).…”
Section: Introductionmentioning
confidence: 86%
“…Procalcitonin (PCT) is currently used as a sepsis diagnostic biomarker, but its performance in critically ill patients has been questioned [4]. Consequently, investigators continue to search for additional sepsis biomarkers that can enhance or complement the diagnostic test characteristics of PCT [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that pathogens may utilize PD-1-related molecules to escape from the host's immune defenses. Recently, several studies have reported a relationship between PD-1-related molecules and critically ill patients who either develop septic shock or are significantly injured (13,14,28). If patients with a high 4.…”
Section: Discussionmentioning
confidence: 97%